(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current study aims to identify the introspective awareness of the study sample, as well as to identify the introspective awareness of the study sample in terms of gender. The researcher adopted the viewpoint of Mehling (2002) as a theoretical framework for Introspective awareness. A sample of (239) male students and (331) female students were chosen randomly from two universities (Baghdad University and Al- Mustansiriyah University). To achieve the objectives of the research, the researcher adopted a vulgar scale (Mehling, 2012), which in its final form consisted of (32) items distributed into eight domains. As for the reliability coefficient of the scale, it reached (0.896) in the Cronbach alpha equation. The study revealed that the research sample has a high introspective awareness. There is a significant difference among the study sample regarding the introspective awareness in terms of gender in favor of females.